Language switching and domain-general control in interpreters - Nour, Soudabeh; Struys, Esli (Frontiers in Language Sciences, 2023)
The purpose of this paper is to examine whether and how training and professional experience in interpreting affect task switching in this bilingual population. In the first experiment, we compared a group of interpreting students to a group of translation students using the bilingual categorization task to assess their domain-specific language switching before and after training. In the second experiment, we added a group of professional interpreters to the participants in experiment 1 to test prepotent response inhibition using the Simon task (domain-general). First, the results showed training-related improvement in the bilingual categorization task in both student groups, indicating a similar effect for translation and interpreting training. Second, both student groups showed better performance on the Simon task compared to professional interpreters, but only on response times and not on accuracy. The correlation analyses of the two tasks in student groups only showed significant correlations between the global RTs and supported the hypothesis that proactive language control may depend more on inhibition than on the switching-specific factor. Considering language background, the lower onset age of L2 acquisition (AOA2) in the interpreting students (compared to the translation students) was significantly correlated with the congruency effect in the Simon task, indicating an impact of language background on domain-general control. Results were discussed in light of the different engaging elements, including task specificity, training length, research method, and participants' linguistic profile.